Transition economies and foreign trade - Winiecki, Jan (Routledge studies of societies in transition, 2002)
Most books on transition economies concentrate on their internal fortunes. Few have analysed the effect that the change in the system has had on foreign trade and export performance - this new book redresses that balance.